carrousel, confessions, confusion. : set 1 / zines 1-3 - Delbeke, Maarten; Boie, Gideon; ETH, Zürich (Londen : Koenig Books, 2019)
Heyvaert, René ; Vinck, Inge ; Dujardin, Filip ; Deleu, luc
Zine 1 Jan De Vylder, René Heyvaert; Zine 2 Peter Swinnen, Luc Deleu, Dépendance Furkapasshöhe; Zine 3 A. Brandlhuber, Dominikus Böhm, St.Peter and Paul Church; Studio Jan de Vylder
boek
Keywords: Studio Jan De Vylder